2020
DOI: 10.3168/jds.2019-17685
|View full text |Cite
|
Sign up to set email alerts
|

Influence of freezing temperature before freeze-drying on the viability of various Lactobacillus plantarum strains

Abstract: Although freeze-drying is an excellent method for preserving microorganisms, it inevitably reduces cell activity and function. Moreover, probiotic strains differ in terms of their sensitivity to the freeze-drying process. Therefore, it is necessary to optimize the variables relevant to this process. The pre-freezing temperature is a critical parameter of the freeze-drying process, but it remains unclear whether the optimal pre-freezing temperature differs among strains and protectants. This study explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 30 publications
1
20
0
2
Order By: Relevance
“… [26] . Pre-stressing cells prior to the freeze drying process is also known to improve the integrity of cells membranes [36] . Another probable explanation for the higher rates of survival obtained by Reddy et al .…”
Section: Results and Discussion Impact Of Cryoprotectants On L Plantarum Over Freeze Dryingmentioning
confidence: 99%
“… [26] . Pre-stressing cells prior to the freeze drying process is also known to improve the integrity of cells membranes [36] . Another probable explanation for the higher rates of survival obtained by Reddy et al .…”
Section: Results and Discussion Impact Of Cryoprotectants On L Plantarum Over Freeze Dryingmentioning
confidence: 99%
“…Carvalho et al (2003b) reported that sorbitol exhibited a considerable protective impact on the survival after freeze‐drying of L. plantarum , L. bulgaricus , and L. rhamnosus . Trehalose also enhanced the maximum survival rates of L. plantarum AR113, WCFS1, and AR307 by 1.25, 1.67, and 6.56 times, respectively, after changing the prefreezing temperature (Wang et al, 2020). However, De Valdez et al (1983) reported that sorbitol and mannitol provided little or no protection of lactococci, lactobacilli, or Leuconostoc due to fast crystallization of substances during the freeze‐drying process.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature was gradually increased from −40°C to 30°C over 36 h, at a pressure of 15 Pa, and freeze-dried with a standard programmed low-speed freeze-drier. The freeze-dried starter cultures were vacuum-packed in foil-laminated bags for storage at 25°C and 30°C for 30 d (Wang et al, 2020).…”
Section: Freeze-drying Of B Lactis Probio-m8mentioning
confidence: 99%